Some Distinctive Features of Narrative Environments - Austin, Tricia (Interiority, 2018)
This paper explores key characteristics of spatial narratives, which are called narrative environments here. Narrative environments can take the form of exhibitions, brand experiences and certain city quarters where stories are deliberately being told in, and through, the space. It is argued that narrative environments can be conceived as being located on a spectrum of narrative practice between media-based narratives and personal life narratives. While watching a screen or reading a book, you are, although often deeply emotionally immersed in a story, always physically ‘outside’ the story. By contrast, you can walk right into a narrative environment, becoming emotionally, intellectually and bodily surrounded by, and implicated in, the narrative. An experience in a narrative environment is, nonetheless, different from everyday experience, where the world, although designed, is not deliberately constituted by others intentionally to imbed and communicate specific stories. The paper proposes a theoretical framework for space as a narrative medium and offers a critical analysis of two case studies of exhibitions, one in a museum and one in the public realm, to support the positioning of narrative environments in the centre of the spectrum of narrative practice.